2004
DOI: 10.2176/nmc.44.112
|View full text |Cite
|
Sign up to set email alerts
|

Radiosurgery for Pituitary Metastases

Abstract: Gamma knife radiosurgery (GKS) was used to treat seven patients with pituitary metastases between November 1994 and February 2003. The diagnoses were based on magnetic resonance imaging and clinical symptoms in six patients and by previous surgery in one patient. The cancer originated in the lung in five patients, and in the breast in two patients. The tumor volume was 0.2 to 9.6 cm 3 (mean 4.0 cm 3 ). The marginal dose was 10 to 14 Gy (mean 11.9 Gy) because of the close proximity to the optic apparatus. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…16,20 Furthermore, at the time of diagnosis, more than half of the patients have systemic metastasis. 9,11,14,18,20 Median survival reported in previous series ranged from 6 to 11 months; 11,13,16,18,20 survival rarely surpassed 3 years. 22 However, in the series of Morita et al, 3 of 36 patients survived at 5 years following diagnosis.…”
Section: Prognosismentioning
confidence: 88%
See 4 more Smart Citations
“…16,20 Furthermore, at the time of diagnosis, more than half of the patients have systemic metastasis. 9,11,14,18,20 Median survival reported in previous series ranged from 6 to 11 months; 11,13,16,18,20 survival rarely surpassed 3 years. 22 However, in the series of Morita et al, 3 of 36 patients survived at 5 years following diagnosis.…”
Section: Prognosismentioning
confidence: 88%
“…Iwai and colleagues reported that 6 of 7 patients achieved regional control and improvement of symptoms after stereotactic radiotherapy with a marginal dosage of 10-14 Gy (mean 11.9 Gy) using the Gamma Knife. 13 Kano et al reported their experience of treating 18 patients who harbored PMs using the Gamma Knife.…”
Section: Treatmentmentioning
confidence: 99%
See 3 more Smart Citations